Religion and the Transmission of COVID-19 in The Netherlands - Paul Vermeer; Joris Kregting (Religions, 2020)
The aim of this study was to find out if the typical spread of hospitalized patients with COVID-19 in The Netherlands, with significantly higher levels in the Dutch Bible belt and the southern, traditionally Catholic provinces, is related to the specific religious composition of the country. To do this, government statistics regarding the level of hospitalized patients with COVID-19 per municipality were combined with statistics regarding church attendance and church membership rates. Results showed that in the Dutch Bible belt the level of patients with COVID-19 was strongly related to church attendance, but in the southern, traditionally Catholic part of The Netherlands nominal church membership mattered more than church attendance. On the basis of these findings, the conclusion was drawn that religion probably facilitates the spread of the virus in both a direct and indirect way. It facilitates the spread of the virus directly through worship services but also indirectly by way of endorsing more general cultural festivities like carnival and maybe even by strengthening certain non-religious social bonds. Epidemiologists monitoring the spread of the virus are called upon to focus more on these possible indirect or latent effects of religion.